Dynamic Model for Axial Motion of Horizontal Pelton Turbine and Validation in Actual Failure Case - C. G. Rodriguez; D. Zambrano; S. Reyes; J. Tapia; M. Egusquiza; E. Egusquiza (Shock and Vibration)
Pelton turbines are important machines for power generation from a renewable energy source such as water. For power rates below 20 MW, the rotor of Pelton turbines is usually in horizontal position. Considering ideal mounting and operating conditions, there are no axial forces acting on the rotor. In practice, there is an hydraulic force due to the difference between nozzle centerline and bucket centerline, and there is a magnetic force due to the difference between axial position of stator and rotor magnetic field centers. These forces are supported by bearings. In this article, a nonlinear dynamic model considering these axial forces and bearings behavior is presented and solved for two different actual Pelton turbines. The nonlinear dynamic model allows determining and evaluating the source of axial motion and therefore provides valuable information in order to reduce it when the axial displacement is high enough to produce damage.